2020
DOI: 10.1523/jneurosci.1742-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake Recruits Tonic Activation of NR2D Subunit-Containing Extrasynaptic NMDARs in Vasopressin Neurons

Abstract: In addition to producing a classical excitatory postsynaptic current via activation of synaptic NMDA receptors (NMDARs), glutamate in the brain also induces a tonic NMDAR current (I NMDA ) via activation of extrasynaptic NMDARs (eNMDARs). However, since Mg 21 blocks NMDARs in nondepolarized neurons, the potential contribution of eNMDARs to the overall neuronal excitatory/inhibitory (E/I) balance remains unknown. Here, we demonstrate that chronic (7 d) salt loading (SL) recruited NR2D subunitcontaining NMDARs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 74 publications
(91 reference statements)
5
11
0
Order By: Relevance
“…4e ) and found that the illumination resulted in inward currents in GFP + neurons under voltage-clamp recording conditions at a holding potential of −65 mV (Fig. 4f ) and the PSCs were blocked by the application of ionotropic glutamate receptor antagonist kynurenic acid 35 (Fig. 4g ), suggesting a glutaminergic synaptic afferent from host neurons to the neurons of grafted organoids.…”
Section: Resultsmentioning
confidence: 92%
“…4e ) and found that the illumination resulted in inward currents in GFP + neurons under voltage-clamp recording conditions at a holding potential of −65 mV (Fig. 4f ) and the PSCs were blocked by the application of ionotropic glutamate receptor antagonist kynurenic acid 35 (Fig. 4g ), suggesting a glutaminergic synaptic afferent from host neurons to the neurons of grafted organoids.…”
Section: Resultsmentioning
confidence: 92%
“…But these same properties also allow NMDA receptors to act as pacemakers, controlling rhythmic firing, e.g., in those circuits involved in breathing, swimming, and walking (Steenland et al, 2008;Li et al, 2010), as well as contributing to the generation of burst firing of reticular thalamic neurons (Deleuze and Huguenard, 2016). The long open times of NMDA receptors, especially those located extrasynaptically, could be contributing to tonic excitation (Sah et al, 1989;Neupane et al, 2021), stabilizing hypothalamic sleep-on neurons in their firing mode. It will be interesting to see whether this role of NMDA receptors generalizes to other sleep-promoting circuits.…”
Section: Discussionmentioning
confidence: 99%
“…One critical factor maintaining sleep could be NMDA-type glutamate receptors. These channels, especially when located extrasynaptically, can provide tonic excitation (Sah et al, 1989;Papouin et al, 2012;Neupane et al, 2021). Indeed, NMDA receptor activation promotes sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The NMDA receptor-mediated tonic current was estimated by holding current difference before and after the application of NMDA receptors antagonists; ifenprodil (IFN; 30 μM, Tocris) and DL-2-Amino-5-phosphonopentanoic acid (DL-AP5; 100 μM, Tocris) as in our previous reports 41 .…”
Section: Spinal Cord Slice Preparation and Electrophysiological Recor...mentioning
confidence: 99%